Task-specific morphological and kinematic differences in Lipizzan horses - Zupan Šemrov, Manja; Přibylová, Lucie; Gobbo, Elena (Frontiers in Veterinary Science, 2025)
IntroductionEquine locomotion emerges from a dynamic interplay between morphology, biomechanics, and functional demands. This study examines the relationship between morphological measurements and gait kinematics in Lipizzan horses, a breed renowned for its diverse work tasks and standardized environmental conditions. These horses offer a unique opportunity to explore task-specific adaptations in biomechanics, with significant implications for breeding strategies and welfare practices.Materials and methodsThe study involved 71 healthy Lipizzan horses that were housed at the Lipica stud farm and performed various work tasks. Morphological measurements were taken with the help of a sartorial meter and an equine measuring stick to determine head and body measurements. Both the left and right sides of the body were measured to ensure consistency. Kinematic data, including regularity, symmetry, cadence, dorsoventral power, propulsion power, stride length and speed, were recorded using the Equimetrix accelerometer at a sampling rate of 100 Hz. The data was collected during several walks and trots where the horses were led over a 50-meter track.ResultsTask-based analysis revealed strong links between morphology and gait in four working groups, with distal limb measurements, especially hoof and pastern lengths, most consistently associated with stride and rhythm parameters. No significant associations were found at the whole-cohort level. Several morphological measurements showed contrasting effects across working groups, and half of the bilaterally measured traits revealed side-specific correlations. The clearest patterns emerged in horses used for general training and riding school. In horses in general training, strong associations were found between distal limb measurements and stride length or cadence, particularly during walk. In riding school horses, broader body measurements were linked to kinematic parameters including propulsion power, dorsoventral power, and symmetry.DiscussionThis study highlights the dynamic interplay between conformation and functional demands in clinically sound horses. Rather than exerting fixed effects, morphological measurements interacted with work type to shape gait expression, even in the absence of pathology. These findings underscore the need to consider both structure and task when evaluating locomotion. Integrating morphometric assessment into training and selection strategies may support performance, soundness, and welfare in healthy working horses.